Catalysing private and public action for climate change mitigation: the World Bank's role in international carbon markets. (2nd January 2021) - Michaelowa, Axel; Michaelowa, Katharina; Shishlov, Igor; Brescia, Dario
ABSTRACT: This policy analysis examines the role of the World Bank in shaping and stimulating international carbon markets. Adopting a public choice perspective, we argue that its engagement can be understood as a response to the joint goal of reputational and financial benefits. The detailed empirical account of the Bank's activities – from its pioneering role through the Prototype Carbon Fund in the early 2000s, to its initiatives for upscaled crediting subsequent to the 2015 Paris Agreement – is broadly in line with this interpretation. The period between 2005 and 2011 most clearly shows that the Bank was ready to forego some reputational benefits for the sake of financial benefits. During this period, it followed a flourishing privately driven carbon market, mostly competing with, rather than catalysing, private activities. After the Paris Agreement opened the door for a new phase of carbon markets, the Bank again took up a pioneering role, now focusing on the public sector. However, since transparency in relation to its activities is limited – thus reducing reputational risk – these activities may not meet the quality standards, notably with respect to additionality, that are a precondition for carbon markets to be an effective tool for climate change mitigation. Key policy insights Over time, the World Bank has alternated between being an 'agenda setter', catalysing private and public sector engagement in carbon markets, and a 'regime follower' regarding international carbon markets, based on varying reputational and financial benefits. In the post-Paris climate regime, the Bank has resumed its original pioneering role, although the scale of its activities is smaller, and they are less transparent, than during the Kyoto Protocol period of the early 2000s. To maximize its contribution, the Bank can act as a source of initial demand for carbon credits, but must have an exit strategy in place once the private and public sector gets sufficiently involved. Sufficient transparency on the Bank's activities is required; reputational considerations provide an incentive to support generation of high-quality carbon credits.